Mathematical modelling of passive discrete lumped parameter system using standard Malaysian rubber constant viscosity - Salim, Mohd Azli; Masripan, Nor Azmmi; Md. Saad, Adzni; Dai, Feng; Noordin, Aminurrashid; Mohd Yusof, Norbazlan (Penerbit UniMAP, 2021)
This paper represents the basic and circular vibration isolator in High Frequencies using Malaysian natural rubber. Rubber material is chosen because it has very high damping to ensure the sufficient dissipation of vibration energy from the seismic wave. They are two methods involve in this paper, which are lumped parameter and wave propagation techniques. The lumped parameter system is developed to represent the baseline model of laminated rubber-metal spring. Wave propagation model is developed using non- dispersive rod. The mathematical modeling of laminated rubber-metal spring has been developed based on the internal resonance, lumped parameter and finite rod model, respectively. For a conclusion, the mathematical modeling of a prediction of basic and circular vibration isolator can be as a tool to predict the new trial-error method for developing new compounding of the vibration isolator in future, respectively.